Evaluation of the Physico-Chemical Quality of Well Water in the Analamanga Region (Antananarivo), Madagascar - Vololonome Bodomalala Razanadrasoa; Jean Rasoarahona; Rado Rasolomampianina; Narindra Ratiarimananjatovo; Rabearisoa Solotiana Rija; Muhammad Ridwan; Koto-Te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The study made in some sites of the Analamanga Region, which are the Fokontany of Mandroseza, Ampanefy, Isaingy, Antalata and Malaho, shows the deterioration of the physico-chemical quality of the water of well. Elements that can cause illnesses for the beneficiaries are detected. The result is marked firstly by the acidity of the well water in all the Fokontany studied, secondly, by the rise in the rates of ammonium and organic matter in the wells which are located in the vicinity of several houses and those of nitrites in samples from wells located in the slums, near fields and rice paddies. Finally, for the Fokontany of Isaingy which is characterized by a very high number of hearths compared to other Fokontany, the waters of the wells are turbid and contain high levels of organic matter, total iron and nitrites.